Patient and Physician Preferences for Treating Adjuvant Melanoma: A Discrete Choice Experiment - Beusterien, K; Middleton, M; Feng Wang, P; Rao, S; Kotapati, S; Sabater, J; Aurora, B; Bridges, J (Scientific Research Publishing, 2017)
Objective: To evaluate and compare patient and physician preferences for the benefits and risks of currently available adjuvant melanoma treatments. Methods: Patients with stage II/III melanoma and oncologists in the USA were recruited from 6 clinical sites and an online panel to complete a survey. Preferences were assessed using a paired comparison discrete choice experiment that allowed for opt-out (i.e. no treatment). The treatments comprised 7 attributes, each with 3 levels associated with pegylated interferon, high-dose interferon, and ipilimumab. Attributes included efficacy outcomes, dosing regimen, and risks of moderate to severe toxicities. In addition, open-ended maximum acceptable risk (MAR) questions assessed tradeoffs between toxicity risk and efficacy. Results: 142 patients (45 stage II; 97 stage III) chose a treatment in 78% of the choice tasks, while physicians (N = 127) chose treatment 79% of the time. The rankings of relative attribute importance were concordant between the patients and physicians for the top 4: 10-year survival in metastatic melanoma, fatigue risk, 3-year recurrence-free survival (RFS), and depression risk. Patients and physicians valued the difference in 21% survival versus no survival benefit about 3 and 4 times as much, respectively, as reducing diarrhea risk from 41% to 1% or reducing depression risk from 40% to 1%. The MAR of severe diarrhea and of a life-threatening event increased as the chance of 3-year RFS increased, with patients reporting higher risks than physicians. Conclusion: Patients and physicians were concordant in their preferences in adjuvant melanoma, preferring treatment versus none and judging potential efficacy to outweigh risks of toxicities.